2014
DOI: 10.1139/cjpp-2014-0307
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric effects of low doses of progesterone on GABA(A) receptor α4 subunit protein expression in the olfactory bulb of female rats

Abstract: The aim of this study was to evaluate the effect of progesterone on the protein expression of ␣4 subunit of GABA(A) receptor, serotonin transporter (SERT), Akt, Erk, and caspase-3 in the olfactory bulb (OB) of female rats exposed to the forced swimming test (FST). Female rats were injected daily with progesterone (0.4 mg/kg body mass) or vehicle during 2 complete oestrous cycles and exposed to the FST, and the protein expression of GABA(A) receptor ␣4 subunit, SERT, Akt, Erk, and caspase-3 in the OB were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Unlike estrogen, there are not extensive data documenting the specific neural systems regulated by progesterone, so it is difficult to propose neurobiological pathways. However, promising data suggest that progesterone may play an important regulatory role in gene expression within several systems (e.g., serotonin, Gamma-Amino Butyric acid) that are thought to be important in anxiety and/or depression (Arbo, Andrade, Osterkamp, Gomez, & Ribeiro, 2014; Bethea & Centeno, 2008; Bethea & Reddy, 2015; Lu, Eshleman, Janowsky, & Bethea, 2003; Quast et al, 2014; Schüle, Nothdurfterb, & Rupprecht, 2014). It is likely that progesterone activates genetic effects via the same mechanisms as those proposed for estrogen during puberty (e.g., differential production of neurotransmitters and/or their receptors), although this possibility awaits investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike estrogen, there are not extensive data documenting the specific neural systems regulated by progesterone, so it is difficult to propose neurobiological pathways. However, promising data suggest that progesterone may play an important regulatory role in gene expression within several systems (e.g., serotonin, Gamma-Amino Butyric acid) that are thought to be important in anxiety and/or depression (Arbo, Andrade, Osterkamp, Gomez, & Ribeiro, 2014; Bethea & Centeno, 2008; Bethea & Reddy, 2015; Lu, Eshleman, Janowsky, & Bethea, 2003; Quast et al, 2014; Schüle, Nothdurfterb, & Rupprecht, 2014). It is likely that progesterone activates genetic effects via the same mechanisms as those proposed for estrogen during puberty (e.g., differential production of neurotransmitters and/or their receptors), although this possibility awaits investigation.…”
Section: Discussionmentioning
confidence: 99%
“…[62] In addition, PROG concentration decreases in female patients with menstrual anxiety, with PROG acting directly on GABA A R or exerting an antianxiety effect by affecting ALLO production. [63][64][65] Studies have confirmed that Gelsemium alkaloids can promote neuroactive steroid synthesis, mainly reflected in upregulated 3α-HSOR gene expression by gelsemine and koumine and TSPO activation by koumine. [34,57] Neuroactive steroids can regulate GlyR and GABA A R activity, causing chloride ion influx, hyperpolarization of the related neuronal cell membrane, and reduced postsynaptic potential, resulting in anxiolytic, sedative, and analgesic effects.…”
Section: Glyr/3α-hsor/allo/gaba a R/hpa Axis Pathwaymentioning
confidence: 95%
“…It also enhanced GABA A R activity in mice, producing anxiolytic effects [62] . In addition, PROG concentration decreases in female patients with menstrual anxiety, with PROG acting directly on GABA A R or exerting an antianxiety effect by affecting ALLO production [63‐65] . Studies have confirmed that Gelsemium alkaloids can promote neuroactive steroid synthesis, mainly reflected in upregulated 3α‐HSOR gene expression by gelsemine and koumine and TSPO activation by koumine [34,57] .…”
Section: Antianxiety‐related Mechanismsmentioning
confidence: 98%
“…Steroid hormones are neuromodulators of GABAA receptors (Gunn et al, 2015) and were shown to activate GABAergic neurons in the lateral septal nucleus in ovariectomized rats (Briski & Singh, 2008). Progesterone produces time-dependent anxiolytic-like effects that have been attributed to both non-genomic factors [e.g., direct or indirect modulation of GABAA receptors and α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid and kainate receptors (Barth, Villringer, & Sacher, 2015) and monoamine release (Tonge & Greengrass, 1971)], and genomic factors (e.g., higher expression of GABAA receptor subunits; Nin et al, 2008;Arbo, Andrade, Osterkamp, Gomez, & Ribeiro, 2014). In the brain, progesterone produces direct or indirect effects.…”
Section: Introductionmentioning
confidence: 99%